2017
DOI: 10.1002/gps.4649
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with brain volume in major depression in older adults without dementia: results from a large autopsy study

Abstract: In this large autopsy study of older adults, MDD was not associated with smaller brain volumes. Regardless of the presence of MDD, in this sample of older adults without dementia, we found that smaller brain volumes were associated with risk factors for brain neurodegeneration such as older age, diabetes, hypertension, and lower education. Copyright © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Further, it should be noted that the depressive symptoms used in this study are not a clinical diagnosis, but a self-reported symptom in a questionnaire. In our analyses, subjects with depressive symptoms showed less BPV at baseline (very weak effect size), which is consistent with previous studies ( Espinoza Oyarce et al, 2020 , Kumar et al, 1998 , Lebedeva et al, 2018 , Nunes et al, 2018 ). On the other hand, our subjects with depressive symptoms showed a decrease in dWMH over time (weak effect size), while several other previous studies have, in a clinical context, associated depression with higher WMH load ( Krishnan et al, 2006 , Nebes et al, 2002 , Teodorczuk et al, 2007 ).…”
Section: Discussionsupporting
confidence: 92%
“…Further, it should be noted that the depressive symptoms used in this study are not a clinical diagnosis, but a self-reported symptom in a questionnaire. In our analyses, subjects with depressive symptoms showed less BPV at baseline (very weak effect size), which is consistent with previous studies ( Espinoza Oyarce et al, 2020 , Kumar et al, 1998 , Lebedeva et al, 2018 , Nunes et al, 2018 ). On the other hand, our subjects with depressive symptoms showed a decrease in dWMH over time (weak effect size), while several other previous studies have, in a clinical context, associated depression with higher WMH load ( Krishnan et al, 2006 , Nebes et al, 2002 , Teodorczuk et al, 2007 ).…”
Section: Discussionsupporting
confidence: 92%
“…Lower brain volume, temporal lobe atrophy, and smaller corpus callosum have been related to the incidence of LLD [ 136 , 137 ], but brain atrophy may also be a consequence of depression, and LLD was associated with right frontal atrophy [ 138 ]. On the other hand, in a large autopsy series of older adults, MDD was not associated with smaller brain volumes [ 139 ]. MRI images in both AD patients with and without depressive symptoms showed cortical thinning in the left parietal and temporal regions.…”
Section: Neurodegenerationmentioning
confidence: 99%
“…Another limitation of the present study was that we could not examine the effect of informant’s distress on NPI scores because the NPI Distress (NPI-D) scale was not available for all the sample. Despite these limitations, other studies with the same methodology for collecting information have been published [4, 13,39, 40].…”
Section: Discussionmentioning
confidence: 99%